A Critical Assessment of 60 Years of Maize Intragenic Recombination - Okagaki, Ron J.; Dukowic-Schulze, Stefanie; Eggleston, William B.; Muehlbauer, Gary J. (Frontiers in Plant Science, 2018)
Until the mid-1950s, it was believed that genetic crossovers did not occur within genes. Crossovers occurred between genes, the “beads on a string” model. Then in 1956, Seymour Benzer published his classic paper describing crossing over within a gene, intragenic recombination. This result from a bacteriophage gene prompted Oliver Nelson to study intragenic recombination in the maize Waxy locus. His studies along with subsequent work by others working with maize and other plants described the outcomes of intragenic recombination and provided some of the earliest evidence that genes, not intergenic regions, were recombination hotspots. High-throughput genotyping approaches have since replaced single gene intragenic studies for characterizing the outcomes of recombination. These large-scale studies confirm that genes, or more generally genic regions, are the most active recombinogenic regions, and suggested a pattern of crossovers similar to the budding yeast Saccharomyces cerevisiae. In S. cerevisiae recombination is initiated by double-strand breaks near transcription start sites of genes producing a polarity gradient where crossovers preferentially resolve at the 5’ end of genes. The findings of preferential recombination at maize gene ends in genomic studies contrasts with older intragenic studies where there was less evidence for either polarity or for double-strand breaks near transcription start sites initiating recombination. Reasons for these different perspectives are due to the different depth and breadth of single locus versus genome-wide studies, and highlight how drawing upon the strengths of both approaches can provide a clearer picture of recombination in maize.